PENGARUH MOTIVASI BERWIRAUSAHA DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA (Studi Pada Mahasiswa Ekonomi Islam Semester VI Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Sumatera Utara) - Rahmansyah, Anugrah Putra; Mulyono, Hardi; Syamsuri, Abd. Rasyid (JURNAL MANAJEMEN AKUNTANSI (JUMSI), 2021)
This research aims to know the influence of motivation of entrepreneurship and entrepreneurial knowledge to the interests of entrepreneurship in students of Islamic Economics Semester VI Faculty of Economics and Business Islam Universitas Islam Negeri Sumatera Utara. The sampling technique using purposive sampling method, namely the sample selected with specific criteria amounted to 175 people. Methods of data collection using the questionnaire. The results of the hypothesis test simultaneously (F Test) variable entrepreneurship motivation and knowledge entrepreneurship have a positive and significant impact on the interest in entrepreneurship. The partial hypothesis test (t Test) variable entrepreneurship motivation and knowledge entrepreneurship have a positive and significant impact on the interest in entrepreneurship. The results of the test of determination obtained the value of R Square of 0,558, meaning that the variables of interest in entrepreneurship can be explained amounted to 55.8% by the variable motivation entrepreneurship and entrepreneurial knowledge, while the remaining 44.2% is explained by other variables not included in this study.